PERTIMBANGAN HAKIM DALAM MENOLAK GANTI RUGI BUNGA MORATOIR BERDASARKAN PASAL 1250 KITAB UNDANG-UNDANG HUKUM PERDATA PADA TRANSAKSI JUAL BELI ANTARA PT ELMECON MULTIKENCANA DENGAN PT AES AGRIVERDE INDONESIA (STUDI PUTUSAN NOMOR : 46/PDT.G/2018/PN.JKT.PST.) - stephen william; Mia Hadiati (Fakultas Hukum Universitas Tarumanagara, 2021)
PT Aes Agriverde Indonesia did not make full payment for the shipment and installation of goods. Panel Distribution Board DB901 (Blower) and DB905 (Lagoon) Repowering PHS and delivery of goods OMM Spare Inverterand PLC PHS Repowering Unit that has been installed, PT Elmecon Multikencana filed a lawsuit to the District Court Central Jakarta for default by PT Aes Agriverde Indonesia. In the lawsuit, one of them is a request for a late fee of 2%. The problem that was raised was how the Judge's consideration of rejecting the interest compensation in Article 1250 of the Civil Code on sale and purchase transactions (Study of Decision Number 46 / Pdt.G / 2018 / PN.Jkt.Pst)? The research method used is a normative research method supported by interview data to strengthen the research results. Whether or not there is an agreement regarding late fees or interest rates that have been submitted to the District Court, it is not impossible or cannot be granted, but it all depends on the judge who will judge at the time the trial begins. It can be concluded that even though the plaintiff does not have a strong legal basis regarding the amount of interest rates, the Panel of Judges at the Central Jakarta District Court should have granted the request for late fees or interest rates.